Gender role attitudes and parents' intention to continue childbearing in Turkey - Serap Kavas (Comparative Population Studies (CPoS), 2021)
It is increasingly acknowledged that gender (in-) equality is one of the most significant factors underlying change in fertility behavior. Researchers have extensively studied the link between gender (in-) equality and fertility decision-making in various settings. However, most of these studies have focused on industrialized countries in North America, Europe, and East Asia, while very few examine this relationship in a non-western, developing country context. Employing individual-level survey data, this paper examines the relationship between parents' gender role attitudes and their fertility intentions for an additional child in urban Turkey, surveyed in 2014. The findings of this study show that parents' attitudes toward gender roles were not an important predictor of fertility decision-making in Turkey. This study suggests that the lack of significant findings supporting the expected association may be related to the measurement of gender role attitudes, suggesting a need to construct a measure that addresses culture-specific aspects of gender roles. This study contributes to the literature by providing a new data point, Turkey, and bringing a comparative perspective to the existing research.
urn:nbn:de:bib-cpos-2021-18en5
Keywords: 300; Fertility decisions; Gender (in)equality; Survey data; Turkey